The Indian Supreme Court’s identity crisis: a constitutional court or a court of appeals? - Khaitan, T (Routledge, 2020)
This article presents an empirical analysis of the Supreme Court’s discretionary appellate jurisdiction (triggered by a “special leave petition” or “SLP”). Based on an analysis of 1100 randomly selected civil SLP cases spread over 11 years, it argues that its expansive SLP docket has cannibalized the Court’s role as an effective constitutional court. It reveals that the admissibility of special leave petitions has a statistically significant relationship with the presence of a “senior advocate” during the admissions hearing. The article emphasizes the need for an institutional separation of the appellate and constitutional functions of the Supreme Court: either as two separate courts or as two separate divisions within a single Supreme Court. It also suggests reducing or eliminating the docket-distorting role of senior advocates – either by taking admission decisions on civil SLPs largely based on written briefs or barring senior advocates from appearing in oral admission hearings for civil SLPs.